(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research discussed an important issue which is related to the human reality in terms of correcting the concepts that have shadows on the movement of society, The concept of peace has transformations that need to be controlled according to Sharia rules so that in order not to be isolated from reality and does not fuse in it according to Sheikh Abdullah bin Bayh’s perspective and his renewed vision.